2008
DOI: 10.1021/ac802262w
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nanoLC LTQ Orbitrap Mass Spectrometric Method for Profiling Glycans Derived from Plasma from Healthy, Benign Tumor Control, and Epithelial Ovarian Cancer Patients

Abstract: We report the development of split-less nano-flow liquid chromatography mass spectrometric analysis of glycans chemically cleaved from glycoproteins in plasma. Porous graphitized carbon operating under reverse-phase conditions and an amide-based stationary phase operating under hydrophilic interaction conditions are quantitatively compared for glycan separation. Both stationary phases demonstrated similar column efficiencies and excellent retention time reproducibility without an internal standard to correct f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 59 publications
1
78
0
Order By: Relevance
“…Typically, MeCN is used as organic modifier in the running buffer for PGC chromatography of free oligosaccharides [4,5,[18][19][20]. Other solvents are only rarely applied [8,21].…”
Section: Acetonitrile As Organic Solventmentioning
confidence: 99%
“…Typically, MeCN is used as organic modifier in the running buffer for PGC chromatography of free oligosaccharides [4,5,[18][19][20]. Other solvents are only rarely applied [8,21].…”
Section: Acetonitrile As Organic Solventmentioning
confidence: 99%
“…Since these structures are produced by different glycosyltransferases, they often have diverging biological implications (43,44). To address this issue, several recent studies have focused on structure-specific chromatographic profiling of glycans (17,18,21,23,24,45,46). These studies utilize structure-sensitive chromatography (typically, either PGC or HILIC) to separate glycans online prior to MS analysis.…”
Section: Glycomics For Biomarker Discovery: Compositional and Structumentioning
confidence: 99%
“…Once separated, specific glycan structures may be identified based on a retention time library (21,47) or by further fragmentation, e.g. by tandem MS (24). The incorporation of chromatographically-derived structure specificity into existing strategies for MS-based glycan biomarker discovery promises to provide highly sensitive and specific biomarkers for many diseases.…”
Section: Glycomics For Biomarker Discovery: Compositional and Structumentioning
confidence: 99%
See 1 more Smart Citation
“…For the untargeted glycomics to identify new glycan biomarkers for a specific disease (Bereman et al 2009) or validate follow-on biologics (Wiegandt and Meyer 2014), LC-MS/MS system has been extensively used. However, these analytical instruments are inappropriate for processing hundreds of samples in parallel at routine diagnostic laboratories or industrial settings after biomarkers or overall glycan structures profiling are identified by LC-MS/ MS (Wu et al 2011).…”
Section: Introductionmentioning
confidence: 99%